Francisella tularensis subsp. holarctica Releases Differentially Loaded Outer Membrane Vesicles Under Various Stress Conditions - Klimentova, Jana; Pavkova, Ivona; Horcickova, Lenka; Bavlovic, Jan; Kofronova, Olga; Benada, Oldrich; Stulik, Jiri (Frontiers in Microbiology, 2019)
Francisella tularensis is a Gram-negative, facultative intracellular bacterium, causing a severe disease called tularemia. It secretes unusually shaped nanotubular outer membrane vesicles (OMV) loaded with number of virulence factors and immunoreactive proteins. In the present study the vesicles were purified from a clinical isolate of subsp. holarctica strain FSC200. We here provide a comprehensive proteomic characterization of OMV using a novel approach in which a comparison of OMV and membrane fraction is performed in order to find proteins selectively enriched in OMV vs. membrane. Only these proteins were further considered to be really involved in the OMV function and/or their exceptional structure. OMV were also isolated from bacteria cultured under various cultivation conditions simulating the diverse environments of F. tularensis life cycle. These included conditions mimicking the milieu inside the mammalian host during inflammation: oxidative stress, low pH and high temperature (42 °C); and in contrast, low temperature (25 °C). We observed several-fold increase in vesiculation rate and significant protein cargo changes for high temperature and low pH. Further proteomic characterization of stress-derived OMV gave us an insight how the bacterium responds to the hostile environment of a mammalian host through the release of differentially loaded OMV. Amongst the proteins preferentially and selectively packed into OMV during stressful cultivations the previously described virulence factors connected to the unique intracellular trafficking of Francisella were detected. Considerable changes were also observed on number of proteins involved in the biosynthesis and metabolism of the bacterial envelope components like O-antigen, lipid A, phospholipids and fatty acids. Data are available via ProteomeXchange with identifier PXD013074.